Identification of Helicobacter spp. in gastric mucosa samples asymptomatic dogs and associate histological alterations - Costa, Manuella Carvalho da; Costa, Paulo Renato dos Santos Costa; Silva, João Carlos Pereira da; Maia, Renner Emerson de Negreiros; Moreira, José do Carmo Lopes (Brazilian Journal of Veterinary Research and Animal Science, 2012)
The objective of the present study was to establish a relationship between the number of spiral bacteria and gastric mucosa histological alterations in mongrel dogs. Endoscopic biopsies of 28 asymptomatic dogs were analyzed. Qualitative evaluation was performed for histological analysis, in which scores from 0 to 3 were attributed, considering the density of spiral bacteria per field (400x), presence of inflammatory cells, number of lymphoid aggregates and existence of gland degenerative alteration. The prevalence of Helicobacter spp., identified by hystological technique (Carbol – fuchsine) and positive urease test, was100%. Eighteen (64.3%) of the 28 dogs presented score 3, and 10 (35.7%0), score 2 for the density of bacteria. The inflammatory infiltrate, predominantly lymphocytic, was slight (score 1) in 17dogs (60.7%) and moderate in 6 (21.4%). From the 28 dogs, 14 (50%) scored 1 for glandular degeneration and 9 (32.1%) scored 0. The body and antrum regions presented the highest positive result to histopathology. Despite the high number of bacteria found in the analyzed samples, the histological alterations have been classified as slight in most of the animals. The presence of Helicobacter spp. apparently does not produces gastritis symptoms.